2011
DOI: 10.1002/chp.20098
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Brokering in Children's Rehabilitation Organizations: Perspectives from Administrators

Abstract: Although administrators were philosophically supportive of knowledge brokering, they identified funding and resource constraints and the absence of evidence of the effectiveness of knowledge brokering as major barriers to the continuation of a KB role in their facility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(80 citation statements)
references
References 14 publications
4
75
1
Order By: Relevance
“…found that knowledge brokers stimulated a peer‐to‐peer learning environment, facilitated cross‐disciplinary learning opportunities and were efficient and effective in transferring knowledge.
‘It was apparent from the interviews that the KB process was perceived by administrators as an efficient and effective way of providing professional development for staff; they considered it relevant to therapists’ day‐to‐day work, time efficient, and a means for integrating new ideas and practices into therapists’ core work responsibilities. The KB brought value by culling through the research and highlighting important and relevant information specific to each facility.’
…”
Section: Resultsmentioning
confidence: 99%
“…found that knowledge brokers stimulated a peer‐to‐peer learning environment, facilitated cross‐disciplinary learning opportunities and were efficient and effective in transferring knowledge.
‘It was apparent from the interviews that the KB process was perceived by administrators as an efficient and effective way of providing professional development for staff; they considered it relevant to therapists’ day‐to‐day work, time efficient, and a means for integrating new ideas and practices into therapists’ core work responsibilities. The KB brought value by culling through the research and highlighting important and relevant information specific to each facility.’
…”
Section: Resultsmentioning
confidence: 99%
“…11 There is, however, a strong focus in the literature on 'knowledge brokers' and other 'mediator' roles, and a growing number of empirical studies [136][137][138][139][140] have investigated these roles. A range of functions has been suggested, including problem definition; research synthesis; facilitating access to research knowledge; developing outputs that are more accessible to users; and developing and brokering networks and other connections.…”
mentioning
confidence: 99%
“…Review of abstracts and/ or titles disqualified a further 1,496 papers that were deemed not potentially relevant to the review objective. We then obtained the remaining 17 papers for detailed review, which resulted in a total of four studies [37][38][39][40] meeting the eligibility criteria (see Figure 1). Two of these studies used mixed methods, one used qualitative methodology, and one used case presentation.…”
Section: Resultsmentioning
confidence: 99%
“…Cameron and colleagues 40 found that paediatric rehabilitation administrators need not only evidence of client and program outcomes but also cost-effectiveness data to build a business case in support of implementing knowledge broker roles. The need for evidence of the benefit of knowledge broker roles is to be expected in a health system with ever increasing fiscal constraints.…”
Section: Discussionmentioning
confidence: 99%